Media sosial dan pengaruhnya: Pengaruh media sosial terhadap kesehatan mental remaja - Nabila, Aghni (Maliki Interdisciplinary Journal, 2024)
Teenage mental health, especially anxiety disorders and depression, can be influenced by social media. Its significant influence can be seen in various aspects of life, from personal relationships to the business sphere. This can have a bad impact because it can cause social pressure that affects mental health. The aim of this research is to determine the influence of social media on adolescent mental health and to determine the potential of social media in promoting mental health. The method used is descriptive qualitative analysis with the study of literature from previous research. The results obtained are that mental health is influenced by internal and external factors. Addiction to social media causes anxiety and thinking disorders for sufferers. however, social media has a positive role in promoting mental health because it can reach a wide audience. The conclusion of this research is that social media has positive and negative influences on mental health, including being a health promotion platform, but if used excessively it will cause anxiety disorders for users.